Understanding conflict and co-existence among Spiti Bhot community and large carnivores in high Himalaya: The case of Himalayan wolves - Lyngdoh, Salvador; Habib, Bilal (Frontiers in Ecology and Evolution, 2022)
The wolves in the Hindukush-Himalayan region belong to one of the most basal lineages of Canis lupus, yet little is known about their ecology and behaviour. In this study, we determine wolf movement and analyse diet patterns in contrast with studies from within its distribution range. We determine conflict perception and identify hotspots using ecological, social, and remotely sensed information. We found wolf diet (n =283 scats) constituted mostly of domestic prey (79.02 %). Wild prey constituted 17.80% of the wolf diet. Interview-based questionnaire surveys revealed that 55% of the respondents claimed to have seen wolves. Over 98% of the respondents claimed wolves as a possible threat to various livestock in the study area. Marginal response curves through the MaxEnt model showed that wolf hotspots were positive in response to their density of location, landuse-landcover, village population, village density, and depredation. Comparisons between scat and questionnaire-based depredation data showed that the perceived levels of depredation by wolves differed significantly from the actual proportion of prey consumed by wolves (χ2 = 99.64, p-value <0.0001). Wolf conflict hotspots showed a very high conflict zone area of 36 km2, high conflict zone, 62 km2, medium conflict zone of 196 km2 and low conflict zone of 3636 km2. Future conflict mitigation strategies may focus on such areas primarily to reduce livestock losses and enhance conservation outcomes. Negative perceptions towards wolves can be managed through a holistic conservation action plan in concert with the existing snow leopard conservation program alongside local traditions that do not hinder livelihood security.